Endemism: differentiation of the concept, methods and application - Noguera-Urbano, Elkin A. (Instituto de Ecología, A.C., 2017)
Endemism is a concept commonly used to identify native taxa or biological groups with restricted range. However, the endemism has different interpretations according to the approach used in the biogeographic analysis (ecological or historical). The multiples interpretations of endemism have led to propose other concepts related with the geographical areas occupied by the endemic taxa (endemic area, area of endemism, center of endemism). In some cases, the results of the technics and protocols used to evaluate the endemism are misinterpreted because in the literature endemic area, area of endemism and center of endemism are used as synonyms. In this order of ideas, this review discusses the concept of endemism, and its application in multiples knowledge fields. The technics and protocols to evaluate the endemism are discussed and compared. It is concluded that it is necessary to use a unified concept of endemism, which could facilitate the interpretation of the endemism in ecology, conservation and biogeography.